2011
DOI: 10.3171/2010.12.jns10912
|View full text |Cite
|
Sign up to set email alerts
|

Primary glioblastoma of the cerebellopontine angle in adults

Abstract: Gliomas are rare entities in the cerebellopontine angle (CPA) in adults. The authors present clinical, neuroradiological, serological, and neuropathological findings in a 60-year-old man with an extraaxial CPA glioblastoma arising from the proximal portion of cranial nerve VIII. The patient presented with progressive left-sided deafness and left-sided facial palsy lasting less than 2 months and progressive dysarthria and dysphagia lasting 2 weeks. Preoperative neuroimaging suggested the diagnosis of CPA mening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 23 publications
1
69
0
1
Order By: Relevance
“…According to the literature, CPA glioblastomas may have different origins [15]. Wu et al [16] reported a CPA glioblastoma that originated from the cranial VIII nerve and reviewed seven other similar cases. Cranial nerve glioblastomas are presumably originated from CNS tissue locating at the root entry zone of the cranial nerve or from heterotopic neuroglia cells in the leptomeninges.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, CPA glioblastomas may have different origins [15]. Wu et al [16] reported a CPA glioblastoma that originated from the cranial VIII nerve and reviewed seven other similar cases. Cranial nerve glioblastomas are presumably originated from CNS tissue locating at the root entry zone of the cranial nerve or from heterotopic neuroglia cells in the leptomeninges.…”
Section: Discussionmentioning
confidence: 99%
“…Such an operation essentially amounts to an amputation of the anterior temporal lobe, and will leave a large resection cavity on the floor of the middle fossa ( Figure 5). Gliomas would not be expected to recur in this resection cavity, as removal of the temporal lobe removes both the normal brain tissue and blood supply necessary to support tumor growth in this area, and leaves behind only dura and overlying calvarium, both very rare sites for glioma growth (Rainov et al, 1996;Gheyi et al, 2004;Wu et al, 2011;Arnautovic, Husain, & Linskey, 2000;Reifenberger et al, 1996;Hsieh et al, 2009;Brandes et al, 1998). The results of our study confirm this theory, as no recurrences involving the temporal lobectomy cavity have been documented after temporal lobectomy with follow up as long as 54 months.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is the most common primary brain tumor in adults, comprising about 20% of all intra cranial tumors8,10). GBM usually arises in the supratentorial region, most commonly cerebral hemispheres8).…”
Section: Introductionmentioning
confidence: 99%
“…GBM usually arises in the supratentorial region, most commonly cerebral hemispheres8). Primary infratentorial GBM is an uncommon disease in adults and rarely found in cerebellopontine angle (CPA), especially8,10). A few cases of GBM arising in CPA have been reported in the literature1,2,57,9,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation